HUBUNGAN KEMAMPUAN BERKOMUNIKASI DOSEN DENGAN MOTIVASI BELAJAR MAHASISWA PENDIDIKAN GURU SEKOLAH DASAR (PGSD) FKIP UNIVERSITAS QUALITY MEDAN - Bernard Simanjuntak (JURNAL CURERE, 2019)
This research was conducted at the Department of Medan Elementary School Teacher Training (PGSD) Quality University Medan in March-April 2018. The study population was all students of PGSD FKIP University of Medan Quality totaling 400 people. Samples using the Random Sampling technique to obtain a sample of 80 students.This type of research is a correlation research using the Product Moment formula from Carl Person on the correlation test, and the t test at a significant level α = 0.05. Based on descriptive and statistical analysis, lecturer communication ability variables characterized by four aspects, namely the ability to communicate orally, communicate in writing, communicate nonverbally, and communicate through tools/media are in the medium category. While the variables of student learning motivation are characterized by diligent & tenacious aspects, aspects of interest, independent aspects, and desire aspects are in the good category.The results of the study showed that the lecturers' communication skills were relatively good with an average score of 36.32. The level of student motivation also tends to be good with an average score of 39.74. Hypothesis testing results obtained rxy > rtable (0,276 > 0,254) and tcount > ttable (2,413 > 1,67). So the hypothesis that says there is a significant positive relationship between the ability to communicate with the students' learning motivation PGSD FKIP University of Medan Quality is accepted.